Durability phenomena of bitumen and bituminous pavement materials - Mohamed, Abdullahi Ali; Soon, Yee Wong; Lau, Teck Leong; Farooqi, Mohd Ahmadullah; Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim; Haryati, Yaacob (Bentham Open, 2021)
The durability of asphaltic mixtures, in addition to traffic loading, is greatly influenced by the extremes environmental parameters. For instance, at higher temperatures, bitumen becomes soft, thereby reducing the stiffness of asphalt mixtures and making them vulnerable to rutting. On the other hand, at lower temperatures, the stiffness of bitumen is increased, reducing the flexibility of asphaltic concrete and rendering it prone to fatigue failure. Therefore, this evaluation is an extensive research study on the durability of binder and asphalt mixture with their phenomena. Besides that, this paper intends to delve into the various testing methods and measures adopted to evaluate aging and slowing it down. It also presents a critical review of these methods and proposes a future course of action to better address aging issues. According to the evaluation, the behavior of bitumen on the basis of its source varies; when it is mixed with bitumen modifiers, aggregates, and other filler materials, its behavior becomes even more complex. Hence the understanding of the phenomenon of aging is important and the significance cannot be overemphasized. Extensive research work has been done over the last seven decades to evolve the understanding of short- and long-term aging and to improve the durability of asphaltic mixtures. Generally, the aging of bitumen under the influence of both environment and traffic is irreversible as well as inevitable. Apart from entailing hefty maintenance budgets, it remains a challenge to the researchers to slow down aging.